METODE QIRĀ’AH DALAM PEMBELAJARAN KETERAMPILAN RESEPTIF BERBAHASA ARAB UNTUK PENDIDIKAN TINGKAT MENENGAH - Khoiriyah, Hidayatul (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2020)
This study aims to determine the implementation of the qirā’ah method in learning Arabic receptive skills for secondary education. The method used is a library research method, while data collection is done by examining and exploring several journal articles, books, and several data sources or other information that are considered relevant to the study. The results of this study are that learning using the    qirā’ah method is an alternative for teachers in teaching Arabic receptive skills (mahārah al-istimā’ and mahārah al-qirā’ah). In learning listening skills (mahārah al-istimā’) students are able to understand the contents of what has been listened to and reveal again through their language both orally and in writing. As for reading skills learning (mahārah al-qirā’ah) students are able to read Arabic texts fluently, are able to translate and are able to understand it well and fluently.